The Rule of Law in Comparative Perspective - Sellers, Mortimer; Tomaszewski, Tadeusz; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This new volume on The Rule of Law in Comparative Perspective compares the different conceptions of the rule of law that have developed in different legal cultures. Lawyers and legal scholars from various legal systems describe the social purposes and practical applications of the rule of law, and how it might be improved in the varied circumstances of their own courts and politics. This book will be of interest to lawyers, judges, public officials, and to all those wishing to improve the fundamental structures of their own legal systems, by bringing equal justice to every person subject to the power of the state.
An Introduction to the Rule of Law in Comparative Perspective -- The Rule of Law in Ancient Greek Thought -- The Liberal State and Criminal Law Reform in Spain -- Some Realism About Legal Certainty in the Globalization of the Rule of Law -- Is Goal-Based Regulation Consistent with the Rule of Law? -- Reflections on Shakespeare and the Rule of Law -- America's Constitutional Rule of Law: Structure and Symbol -- Constitutions Without Constitutionalism: The Failure of Constitutionalism in Brazil -- Rule of Law, Power Distribution, and the Problem of Faction in Conflict Interventions -- The Rule of Law in Transitional Justice: The Fujimori Trial in Peru -- The Interaction of Customary Law with the Modern Rule of Law in Albania and Kosova -- Dualism, Domestic Courts, and the Rule of International Law.
Keywords: Law; Philosophy of law; Comparative law; Constitutional law; Law; International & Foreign Law/Comparative Law; General Law/Fundamentals.; Philosophy of Law; Constitutional Law; Law, general